2017
DOI: 10.1021/acs.analchem.7b00353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Three Epoetin Alpha Products by LC and LC-MS Indicates Differences in Glycosylation Critical Quality Attributes, Including Sialic Acid Content

Abstract: Erythropoietin (EPO) is one of the main therapeutics used to treat anemic patients, greatly improving their quality of life. In this study, biosimilars Binocrit and a development product, called here CIGB-EPO, were compared to the originator product, Eprex. All three are epoetin alpha products, reputed to have similar glycosylation profiles. The quality, safety, and efficacy of this biotherapeutic depend on the following glycosylation critical quality attributes (GCQAs): sialylation, N-glycolyl-neuraminic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Our data showed that the degree of O-acetylation of sialic acid in JR-131 differs to some extent from that of darbepoetin alfa, which may affect in vivo clearance [16]. However, the pharmacokinetic parameters in humans including plasma t 1/2 are similar for the two drugs PLOS ONE [20], and the erythropoiesis-stimulating activity of these products in the model rats was not different (Fig 9), indicating that this glycan variation does not affect the pharmacokinetics and in vivo efficacy of the two drugs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our data showed that the degree of O-acetylation of sialic acid in JR-131 differs to some extent from that of darbepoetin alfa, which may affect in vivo clearance [16]. However, the pharmacokinetic parameters in humans including plasma t 1/2 are similar for the two drugs PLOS ONE [20], and the erythropoiesis-stimulating activity of these products in the model rats was not different (Fig 9), indicating that this glycan variation does not affect the pharmacokinetics and in vivo efficacy of the two drugs.…”
Section: Discussionmentioning
confidence: 69%
“…The dominant glycan compositions contain sialylated tetra-antennary structures (Gal 4 GlcNAc 4 Fuc 1 NeuAc 4 Man 3 GlcNAc 2 ) at all glycosylation sites. Although the major peaks were not different between JR-131 and the originator, the signal intensities of the O-acetylated sialic acid ion-derived subpeaks were somewhat different (S2A- S2C Fig), which indicates that JR-131 contains less O-acetylated sialic acid than darbepoetin alfa and this may affect the therapeutic half-life of these drugs [16].…”
Section: Glycosylationmentioning
confidence: 92%
“…Glycoprotein digestion with neuraminidase and subsequent UPLC or MS analysis could provide information about presence and amount of sialic acids [64,65], and other exoglycosidase digestions are used for characterization of other glycan moieties [67,68]. Additionally, level of sialic acids (Neu5Ac, Neu5Gc, and O-acetylated sialic acids) could be determined by mild hydrolysis and subsequent labeling with 1,2-diamino-4,5-methylenedioxybenzene using a kit developed by Ludger Ltd, which has recently been used in analysis of three epoetin alpha products [69].…”
Section: Methods For N-glycan Release From Therapeutic Glycoproteinsmentioning
confidence: 99%
“…On the other hand, O-glycans released by other methods may be fluorescently labeled. Several fluorescent labels have been described for glycan labeling for glycoproteins: 2-aminopyridine (PA) [78], 2-aminobenzoic acid (2-AA) [79,80], 2-aminobenzamide (2-AB) [56,81], procainamide (4amino-N-(2-diethylaminoethyl) benzamide) [69,82] and more recently aminoquinoline carbamate (AQC) [44] and RapiFluor-MS (Waters) for the UPLC and MS techniques. For CGE-LIF, 8-aminopyrene-1,3,6-trisulfonate (APTS) and 2-amino-1-naphthalenesulfonic acid (2-ANSA) can be used.…”
Section: Fluorescent Labeling Of N-glycans and O-glycansmentioning
confidence: 99%
“…Most recently chromatography has been employed to provide a means for the separation, identification and subsequent quantification of sialic acids in biological [64][65][66] and other samples such as infant formula 67 and milk products. 68 For the analysis of sialic acids, derivatisation is required using fluorescent labels and reverse phase chromatography is employed to separate the sialic acids from the bulk material and from each other, allowing closer scrutiny of a variety of sialic acid derivatives in one sample.…”
Section: Chromatographic and Mass Spectrometric Assays For The Determination Of Sialic Acidmentioning
confidence: 99%